Fuels and Fire Behavior in a Sierra Nevada Mixed-Conifer Forest - Christal Johnson; Sophan Chhin; Jianwei Zhang (Journal of Forest and Environmental Science, 2025)
After a past history of fire suppression, California’s forests face increased fire risk from the buildup of fuels. The objective of the study is to develop custom fuel models for the area and to determine whether fuel loads differ significantly by dominant species, and whether measured fuel loads differ from the closest standard fuel models. Measurements of fuel loads suggested that stands dominated by a sugar pine (Pinus lambertiana) had significantly higher loads of fine fuels than ponderosa pine (Pinus ponderosa). Based on fire modeling, sugar pine may also show more severe fire behavior than ponderosa. Standard fuel models did not closely correspond to the custom fuel models in either fuel loads or predicted fire behavior, suggesting a need for further development of new fuel models. Existing fuel models fail to reflect the fuel loads measured in Lassen National Forest, and lead to different predictions of fire behavior. Evidence also suggests that fuel loads and fuel bed density differ based on species composition. This study also highlights the possible under-prediction bias found in many custom fuel models and models of crown fires. More detailed measurements of ladder fuels and crown characteristics are required for more accurate modeling of crown fire behavior.